The Preparation and Evaluation of a Standardized Fibrin Plate for the Assessment of Fibrinolytic Activity - Bishop, R; Ekert, H; Gilchrist, G; Shanbrom, E; Fekete, L (Thrombosis and Haemostasis, 1970)
A new fibrin plate technic for evaluating components of the fibrinolytic system has been developed. It provides quick, accurate, and easily interpreted results for the fibrinolytic profile. The standardized human plasminogen-free fibrin plates can be produced in bulk and stored for prolonged periods of time. A test specimen placed in a well punched in the buffered agarose gel diffuses into the agar and lyses the fibrin clot, forming a clear reaction zone. The zone diameter is directly proportional to the log of the percent concentration of available fibrinolytic enzyme in the specimen. The plates may be used to quantitate total plasminogen, and estimate available plasmin and active plasmin. A good correlation between results obtained using these fibrin plates and caseinolytic methods was found. Performance and interpretation of tests of fibrinolysis done on these new fibrin plates indicate that it may be the most sensitive technic available for clinical laboratory work.